'Gemah Ripah', Bank Sampah Berbasis Masyarakat di Pedukuhan Badegan, bantul, Provinsi Daerah Istimewa Yogyakarta - Bambang Suwerda; Yamtana Yamtana (Sanitasi: Jurnal Kesehatan Lingkungan, 2009)
Waste still a great concern of people and needs comprehensive solution. According to Act No.18/2008 about Waste Management, self-sorting on wastes yielded by households are emphasized and endorsed. In order to solve the waste problems in Badegan Village, the concept of Waste Bank are introduced, of which people do the process of sorting, deposit the waste to the bank, and receipt some money which were directly put into their savings. Some steps were conducted to develop the program, i.e. socializing the program to differentgroups of community, setting-up the management board, coordinating with Badegan environmental health workshop and third-parties, training of officers, and conducting ongoing monitoring and evaluation. On 5th June 2008, ’Gemah Ripah’ Waste Bank was founded. In the first seven months it succesfully gained 87 active members. It is hoped that the Bank is becoming a model for wastemanagement in Bantul Regency, and in the future the program would be accepted, copied and implemented in other areas.